ANTIBIOTIC RESISTANCE PATTERN OF ACINETOBACTER BAUMANNII ISOLATED FROM BACTEREMIA PATIENTS IN PAKISTAN - Jabeen, Fauzia; Khan, Zaman; Muhammad Sohail; Tahir, Ali; Tipu, Imran; Saleem, Hafiz Ghulam Murtaza (Journal of Ayub Medical College Abbottabad, 2022)
Background: Acinetobacter baumannii causes a number of life threatening infections in Hospitalized patients attributed to its ability to develop resistance against multiple antibiotics. The current scrutinisation is aimed to observe the prevalence and antibiotic resistance profile of A. baumannii strains isolated from blood of tertiary care Hospitalized patients in Lahore, Pakistan. Methods: This research is a retrospective study conducted over a period of one year where 1864 blood samples were collected from both male and female patients with septicaemia. Total 156 A. baumannii species were identified by conventional method and their antimicrobial resistance pattern against 22 antimicrobials (representing all known classes of antibiotics) was evaluated by Kirby Bauer disc diffusion method. MICs of colistin, polymyxin B and vancomycin against A. baumannii were calculated by E test and broth dilution method. Results: More males (n=97, 62%) were found infected than females (n=59, 38%). The spreading rate of A. baumannii was highest (n=101, 65%) in patients of age ‰¤20 years, and lowest (n=12, 7%) in the patients with the age of 41-60 years. Most of the strains of A. baumannii (n=118, 75.6%) were found to be MDR (multi drug resistant), 37 (23.7%) strains were XDR (Extensively drug-resistant) and only 1 (0.05%) strain was PDR (pandrug resistant). All the strains were sensitive to minocycline and tigecycline whereas highest non-susceptibility (n=144, 92%) was seen against Ampicillin-Sulbactam. Most of the strains demonstrated resistance against carbapenem and cephalosporin beckoning that A. baumannii can no longer be considered for salvage therapy by carbapenem. MICs of colistin, polymyxin B and vancomycin against A. baumannii divulged polymixin B as the most effective drug. Conclusion: Use of wide range of drugs has made A. baumannii multidrug resistant. Colistin, polymyxin B and vancomycin are the preferable drugs for the treatment of A. baumannii infections.